Spinal Nerve Root Haemangioblastoma Associated with Reactive Polycythemia - Eric K. C. Law; Ryan K. L. Lee; James F. Griffith; Deyond Y. W. Siu; Ho Keung Ng (Case Reports in Radiology)
Haemangioblastomas are uncommon tumours that usually occur in the cerebellum and, less commonly, in the intramedullary spinal cord. The extramedullary spinal canal is an uncommon location for these tumours. Also haemangioblastoma at this site is not known to be associated with polycythemia. We present the clinical, imaging, and histological findings of an adult patient with extramedullary spinal haemangioblastoma and reactive polycythemia. Radiography and computed tomography (CT) revealed a medium-sized tumour that most likely arose from an extramedullary spinal nerve root. This tumour appeared to be slow growing as evidenced by the accompanying well-defined bony resorption with a sclerotic rim and mild neural foraminal widening. Magnetic resonance imaging revealed prominent flow voids consistent with tumoural hypervascularity. CT-guided biopsy was performed. Although preoperative angiographic embolisation was technically successful, excessive intraoperative tumour bleeding necessitated tumour debulking rather than complete tumour resection. Histology of the resected specimen revealed haemangioblastoma. Seven months postoperatively, the patients back pain and polycythemia have resolved.